2014
DOI: 10.18261/issn1891-943x-2014-04-03
|View full text |Cite
|
Sign up to set email alerts
|

Development of Student Teachers’ Digital Competence in Teacher Education - A Literature Review

Abstract: This article is a literature review of online peer-reviewed empirical studies from 2000 to 2013 regarding the development of digital competence of student teachers in teacher education qualified to teach in the secondary school grade level. The purpose of the review is to showcase and establish knowledge about empirical research on ICT-training in teacher education, and contribute with an overview of approaches for researchers, teacher educators, and policymakers on how teacher education develop student teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(99 citation statements)
references
References 83 publications
5
85
0
9
Order By: Relevance
“…They include both cognitive and technical aspects. However, it should be stressed that the use of digital technologies in teaching differs significantly from other professions [24,25]. In the context of education sciences, the digital competences of a student, as a future teacher, also include good pedagogical and didactic evaluation and understanding the impact of digital technologies on learning strategies and the digital Bildung of pupils and students [26].…”
Section: Pedagogical Entrepreneurship In the Remote Study Processmentioning
confidence: 99%
“…They include both cognitive and technical aspects. However, it should be stressed that the use of digital technologies in teaching differs significantly from other professions [24,25]. In the context of education sciences, the digital competences of a student, as a future teacher, also include good pedagogical and didactic evaluation and understanding the impact of digital technologies on learning strategies and the digital Bildung of pupils and students [26].…”
Section: Pedagogical Entrepreneurship In the Remote Study Processmentioning
confidence: 99%
“…Being digitally competent means to have various skills (e.g., cognitive, emotional and practical) for using digital devices (Eshet-Alkali & Amichai-Hamburger, 2004). Teachers' use of such devices might differ from the use of the devices in other professions, as the use requires adequate pedagogic-didactic evaluation and an awareness of its implications for learning (e.g., Røkenes & Krumsvik, 2014). Tømte (2013) found that the use of digital devices as part of a discipline makes up part of teaching practice at teacher education institutions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…More recently, Røkenes and Krumsvik (2014) reviewed a vast number of studies on teachers’ use of ICT in the classroom, revealing that the effectiveness of implementing ICT in schools may partly rely on Students’ digital competence ( Røkenes and Krumsvik, 2014 ; Wu et al, 2022 ) as well as on how effectively teachers can implement and use ICT for teaching and learning. Indeed, strong correlations have been found between teachers’ digital competence and Students’ subject learning outcomes in Norwegian secondary schools ( Røkenes and Krumsvik, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Røkenes and Krumsvik (2014) reviewed a vast number of studies on teachers’ use of ICT in the classroom, revealing that the effectiveness of implementing ICT in schools may partly rely on Students’ digital competence ( Røkenes and Krumsvik, 2014 ; Wu et al, 2022 ) as well as on how effectively teachers can implement and use ICT for teaching and learning. Indeed, strong correlations have been found between teachers’ digital competence and Students’ subject learning outcomes in Norwegian secondary schools ( Røkenes and Krumsvik, 2014 ). ICT in education can be used for a variety of different purposes, such as active teaching and learning through Students’ involvement ( Ghavifekr and Quan, 2020 ), improving Students’ understanding of key concepts or developing content knowledge and specific abilities, as well as a correlating improvement in their learning results ( Furman et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%